Measuring Labour and Rethinking Value - Adkins, Lisa (feminists@law, 2014)
In this lecture Lisa Adkins considers the form of labour which has been at the very heart of feminist theorizations of immaterial labour, namely domestic labour. She considers transformations to this labour in the context of financialization, and in particular the direct links which are being forged between domestic labour and the creation of financial value. Adkins considers the implications of these links, or more precisely, of the financialization of domestic labour, for the current state and future of the relations of social reproduction.